Решите уравнение: 7х – (х+3) = 2(2х – 1)

ulianakosovska0 ulianakosovska0    3   23.08.2019 16:30    2

Ответы
SMILЕ31 SMILЕ31  05.10.2020 14:55

7х-(х+3)=3(2х-1)

7х-х-3=6х-3

7х-х-6х=-3+3

0=0, при любом значении х равенство будет верным 

ПОКАЗАТЬ ОТВЕТЫ
PolinaCartonova PolinaCartonova  05.10.2020 14:55
7х - (х+3) = 2(2х-1)
7х - х - 3 = 4х - 2
6х - 4х = 3 - 2
2х = 1
х = 1 : 2
х = 0,5
Проверка
7 · 0,5 - (0,5 + 3) = 2·(2 · 0,5 - 1)
3,5 - 3,5 = 2·(1 - 1)
0 = 2 · 0
0 = 0 
ответ: х = 0,5
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра